Accessibility of school facilities for students with disabilities following the law on persons with disabilities - Amrullah, Muhammad Karim (COPE: Caraka Olah Pikir Edukatif, 2025)
The Law on Persons with Disabilities mandates accessibility of facilities for people with disabilities in various sectors and spaces, including in the education sector in schools. The mandate for accessibility of school facilities is in line with several related laws and regulations. This mandate must be understood by the central government, local governments, educators, education personnel, and educational unit administrators so that they can serve students with disabilities. This research employed qualitative methods, normative legal research, a statutory approach, and descriptive analysis. Data collection techniques were carried out through literature studies. This article describes the mandate for accessibility of facilities in schools according to the Law on Persons with Disabilities and related laws and regulations. This research aims to facilitate understanding for the parties given the mandate, so it is hoped that related services for students with disabilities can be fulfilled properly. The mandate consists of at least physical and non-physical accessibility that should be available in schools, along with other related matters